Synchronous colonic malignancy - Hake, Prasad Dasharath; Umale, Narayan Pundalik; Yadgire, Atul Uttamrao; Sarda, Kaustubh Madhusudan (International Journal of Research in Medical Sciences, 2016)
Synchronous colorectal neoplasias, defined as 2 or more primary tumors identified in the same patient and at the same time, are caused by common genetic and environmental factors. Since intraoperative palpation can miss up to 69% of the SN, currently, synchronous neoplastic lesions are usually diagnosed at a preoperative staging by colonoscopy or virtual colonoscopy; according to data from literature, 3% of the patients with SN are affected by different types of malignant lesions while 33-55% shows villous adenomas. Literature also confirms the presence of primitive synchronous cancers; malignant synchronous lesions are very rare, showing the following incidence: between 0,17% and 0.69% in case of 2-3 synchronous lesions, 0.19% in case of 4-5 synchronous lesions. The most voluminous synchronous cancer is called "first primitive" or "index" cancer. When the index cancer is located in the caecum, the incidence of left colon synchronous cancers is higher than when the index cancer is located in the left colon. Colorectal adenomas standard treatment is usually represented by endoscopic polypectomy; indeed only 5% of synchronous colorectal lesions require a surgical treatment.